THE INFLUENCE OF INFORMATION TECHNOLOGY ON THE PERFORMANCE EFFICIENCY OF EMPLOYEES AT TOTO KABILA REGIONAL PUBLIC HOSPITAL (Journal of Health, Technology and Science (JHTS), 2025)
This study aims to determine the effect of information technology on Employee Performance efficiency at the Toto Kabila Regional General Hospital, and analyse the extent to which the use of information technology can improve Employee Performance efficiency in the hospital environment. This research method uses a quantitative research approach, descriptive research type, using data collection techniques based on questionnaires.The results showed that based on the analysis of the statistical test Chi-Square carried out, it resulted in a Pearson Chi-Square value with a significance level of 0.000 (p < 0.05), which indicates a significant influence between information technology and Employee Performance efficiency at Toto Kabila Regional General Hospital. Thus, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted, so it can be concluded that there is a positive and significant influence of the application of information technology on Employee Performance efficiency.Keywords: Information Technology, Performance, Efficiency